A dual‐band dual‐polarization Fabry–Pérot resonator antenna. Issue 4 (10th February 2022) - Xu, He; Zhao, Gang; Tian, Chao; Zhou, Shi‐Guo; Jiang, Xu‐Hong
Abstract: A novel dual‐band dual‐polarization Fabry‐Pérot resonator antenna (FPRA) is presented, which is composed of double‐layer frequency selective surfaces (FSS1 and FSS2) and planar patch antenna. By analyzing the passband and stopband characteristics of the FSS1 and the FSS2, it is revealed that FSS1 has stopband characteristic for low frequency and passband characteristic for high frequency, while FSS2 shows stopband characteristic for high frequency and passband characteristic for low frequency. Based on these traits, the gain is improved by the high‐reflection coefficient of FSS1 at low frequency. The linear to circular polarization (CP) conversion is achieved by FSS2 at high frequency. To verify the performance of this proposed design, a prototype FPRA is fabricated and measured. The measurement results show that the peak gain of antenna reaches 16.1 dBic with CP at 9.4 GHz and 15.3 dBi with linear polarization at 5.6 GHz. The measured 3‐dB gain bandwidths is from 5.35 GHz to 5.8 GHz in the lower band, and the combined fractional bandwidth (−10 dB impedance matching, 3‐dB measured gain, and 3‐dB axial ratio) from 9.27 to 9.55 GHz in the upper band is achieved.